The language of the Third Reich by Victor Klemperer with regard to translations: an experience report - Dimova, Ana (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
The paper analyzes the language of the Third Reich, as portrayed by Victor Klemperer in his LTI, Lingua Tertii Imperii: A Philologist’s Notebook, by focusing on three terms that were foundational for the National Socialist ideology and its social practices: Reich, Gefolgschaft, and Gleichschaltung. For translation, they pose a problem as they were strongly ideologically conditioned and firmly bound to the German language, hence lacking equivalents in most languages. In translation, these culturally specific terms are typically rendered through loan words or are calqued. In cases where functional analogies were used in translation, intriguing historical or ideological similarities can be observed in different languages and cultures. The translatological analysis is based on translations into Bulgarian, Russian, and English.
Keywords: Victor Klemperer; the language of the Third Reich; translation; cultural specifics